JANUARI EFFECT IN THE INDONESIAN STOCK EXCHANGE: COMPARISON OF BIG AND SMALL CAP STOCKS - Japlani, Ardiansyah (JURNAL AKUISISI, 2015)
Researchers have detected in the financial markets the presence of the January effect, which refers to the historical patterns of higher returns in January than that of the other months(Feb-Dec). This study investigates that the exixtence of January effect on small capitalization stocks is much stronger than the big capitalization stocks in Indonesian stock exchange. We found that there is no January effect in Indonesian Stock Exchange. We explain this phenomenon by examining all stocks, as measured by the t test and analysis regression of dummy. We still use the similiar procedure by using t test and dummy regression, but the sample is divided into big and small capitalization stocks. We found that the January effect is stronger for big capitalization stocks than the small capitalization stocks.Â Keywords: Stock returns, Big capitalization stocks, small capitalization stocks, T test, and Regression of dummy.